Modified small-scale batch procedure for isolation of dsRNA from Cryphonectria parasitica - Libantová, Jana; Moravčíková, Jana; Adamčíková, Katarína; Kobza, Marek; Juhásová, Gabriela (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2007)
Cytoplasmically-transmissible viral double-stranded RNAs of the genus Hypovirus cause reduced virulence (hypovirulence) in the chestnut blight fungus Cryphonectria parasitica. Biological control of this fungal disease is done by inoculating selected artificial hypovirulent strains of C. parasitica in the wounds of attacked chestnut trees and is followed by testing the transmissibility of dsRNA to C. parasitica isolates affecting these trees. Here we present a modified protocol of isolation and detection of dsRNA. The proposed procedure requires smaller amounts of fungal material for dsRNA detection and uses less reagents, thus resulting in appreciable cost savings.